Differences in user experience comparing virtual reality and screen based interactions: Comparing user experiences when making design choices for prefabricated houses using either a virtual reality or screen based system - DAVIDSSON, RASMUS; DEHMER ÖSTEBO, MARTIN (My University, 2019)
Virtual reality (VR) is an increasingly popular technology among the public but it is also fairly new in that the latest era of modern VR devices are not more than five to seven years old. This has led to a significant difference in knowledge on how users experience VR interactions differently compared to screen based counterparts. This study investigates what factors of interaction benefits from being experienced through VR rather than a screen based system. The factors the study is based on are perception, understanding and confidence. A system which allows users to make design choices in the process of buying a prefabricated house was chosen for this investigation and a prototype of a VR system allowing for this was designed. Due to VR being a new field of research, there are few guidelines which can be followed in VR design. Therefore, the study also investigates guidelines for design of VR systems intended for inexperienced users. Halfway through the process a user test was held in order to make improvements to the VR prototype and find guidelines for design. Six guidelines were found from analysis of the tests results. In a second test, interaction with the VR prototype was compared to a screen based version of the same system. Analysis of data from this test found six system dimensions in which VR and screen based systems differ, of these all but one were perception based. These results show that users of VR experience visualizations differently than users of a screen based system. VR users experience that visual properties of design choices are of greater importance and they have an increased spatial understanding of the digital environment. A difference in how understanding and confidence could not be found.
Keywords: VR; design choices; interaction design; interface design; prefabricated houses; unreal engine 4; user experience